Massa de forragem, composição química do capim-massai e comportamento ingestivo de ovinos durante a fase de implantação do eucalipto em sistema silvipastoril - Andrade, Nomaiací de [UNESP] (2014)
The implementation of silvopastoral system is increasing because of its potential to increase soil fertility, improve forage quality, promote thermal comfort, and provide diversification of income for the producer, achieving higher efficiency of animal production systems. The objective of this study was to determine the effects of silvopastoral system at different spacings of eucalyptus tree species in the development of eucalyptus, productivity of massaigrass and grazing behavior of sheep under intermittent grazing at conditions Jaboticabal - SP. The experiment consisted of three treatments with four replicates, varying the spacing between the rows of eucalyptus, these being: no shade (control treatment), presence of trees spaced 6 meters and 12 meters spacing. The variables: time (pre-and post-grazing), grazed stratum bulk density, rate of net accumulation, leaf / stem ratio, morphological components (dry mass of leaves, stem dry mass, dry mass of dead material), total dry forage chemical composition of the sample in simulated grazing, animal behavior and monitoring of eucalyptus. The analyzes of response variables massaigrass were performed according to a randomized block design with six replications in a repeated measures scheme. The height of eucalyptus has been reported in completely randomized blocks. Treatments were considered fixed effects and grazing cycles as random. The grass-massai physiologically responded to photoperiod decreased over the grazing cycles, resulting in significant effects (P <0.10) in morphological components, promoting the issuance of inflorescences. We observed higher mean crude protein on the first day collection on the third day compared with 8.04% and 5.29%, respectively, in the treatment of 6 meters. The treatments differed (P <0.10) for protein content, with the highest average observed in the treatment of 6 meters. The dry matter showed a linear effect (P <0.10) over the cycles, the third day ...